2001
DOI: 10.1023/a:1010676111026
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Leaves of Vicia faba were collected from the field and the greenhouse and transmittance of epidermal peels from adaxial and abaxial sides was determined in the wavelength range from 250 to 800 nm using a spectrophotometer equipped for the measurement of turbid samples. From the same leaves, epidermal transmittance was estimated by a recently developed fluorometric method. Both methods gave highly correlated results with a slope of the regression line between both methods close to 1 and an intercept close to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Increasing flavonoid levels in the leaf, however, do not necessarily correspond with improved epidermal UV screening because considerable fractions of flavonoids are located in the mesophyll in some plant species (Burchard et al 2000;Rozema et al 2002;Semerdjieva et al 2003). Studies combining flavonoid quantification with measurements of epidermal transmission for UV radiation, however, have indicated that flavonoid levels increased by UV radiation result in improved UV screening (Burchard et al 2000;Mazza et al 2000;Bilger et al 2001;Kolb et al 2001;Markstädter et al 2001;Krause et al 2003). This is consistent with the view that natural UV-B intensities reduce epidermal UV transmittance by stimulating synthesis of epidermal flavonoids.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Increasing flavonoid levels in the leaf, however, do not necessarily correspond with improved epidermal UV screening because considerable fractions of flavonoids are located in the mesophyll in some plant species (Burchard et al 2000;Rozema et al 2002;Semerdjieva et al 2003). Studies combining flavonoid quantification with measurements of epidermal transmission for UV radiation, however, have indicated that flavonoid levels increased by UV radiation result in improved UV screening (Burchard et al 2000;Mazza et al 2000;Bilger et al 2001;Kolb et al 2001;Markstädter et al 2001;Krause et al 2003). This is consistent with the view that natural UV-B intensities reduce epidermal UV transmittance by stimulating synthesis of epidermal flavonoids.…”
Section: Introductionmentioning
confidence: 67%
“…Kolb et al 2001). The degree to which hydroxycinnamic acids support flavonoid screening, however, differs markedly between species; they contribute minimally to UV-B screening in leaves of Vicia faba (Markstädter et al 2001), but considerably in Arabidopsis thaliana and grapevine (Landry et al 1995;Sheahan 1996;Kolb et al 2001). Further, in primary leaves of rye (Secale cereale), the importance of hydroxycinnamic acids for UV screening depends on the developmental stage (Burchard et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study (Krause et al 1999a), a small increase in UV-absorbing compounds obtained by 0.5 h d~ ' sun exposure of shade-grown plants of Virola surinamensis resulted in effective protection of PSII against solar UV-B. Probably relatively small amounts of protective substances suffice when they are accumulated in the adaxial leaf epidermis (Markstädter et al 2001). As recently reported by Liakoura et al (2003), shade leaves of Mediterranean woody plants were perfectly protected against UV-B by their epidermis, although leaf extracts exhibited much lower UV absorbance than those obtained from sun leaves.…”
Section: Discussionmentioning
confidence: 94%
“…Ideally it should be a leaf without epidermis with an equal excitation of Chl fluorescence at 650 nm (red) and 375 nm (UV-A) (Barnes et al 2000). Markstädter et al (2001) propose to divide the measurements on the sample by the identical measurement (same device, same conditions) of peeled leaves or, if leaf peeling is not possible, a blue foil standard that has fluorescence properties similar to that of leaves (Kolb et al 2001, Markstädter et al 2001). The standard blue fluorescent foil used by FORCE-A has different spectral characteristics than Chl in vivo.…”
Section: Resultsmentioning
confidence: 99%